2008
DOI: 10.1007/s10763-008-9142-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Senior High School Students’ Misconceptions About Statistical Correlation, and Their Possible Causes: An Exploratory Study Using Concept Mapping With Interviews

Abstract: Correlation is an essential concept in statistics; however, students may hold misconceptions about correlation, even after receiving instruction. This study aimed to elucidate (1) the misconceptions held by senior high school students about correlation, using the tool of concept mapping along with interviewing, (2) the possible causes of these misconceptions, and (3) the effectiveness, advantages, and limitations of the adopted concept mapping using an interviewing technique for identifying student misconcepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In addition, the refutation text contained information challenging four misconceptions about covariance: (1) covariance is related to the slope of the fit line, (2) covariance implies causality, (3) zero covariance proves the absence of any association, and (4) covariance is a standardized statistic. These misconceptions were identified to be particularly prevalent among learners in previous research (e.g., Authors, 2018;Batanero, Estepa, & Godino, 1996;Liu et al, 2009). For each misconception, the three typical elements of a refutation text passage were provided (see, e.g., Tippett, 2010): First, one sentence described the misconception.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the refutation text contained information challenging four misconceptions about covariance: (1) covariance is related to the slope of the fit line, (2) covariance implies causality, (3) zero covariance proves the absence of any association, and (4) covariance is a standardized statistic. These misconceptions were identified to be particularly prevalent among learners in previous research (e.g., Authors, 2018;Batanero, Estepa, & Godino, 1996;Liu et al, 2009). For each misconception, the three typical elements of a refutation text passage were provided (see, e.g., Tippett, 2010): First, one sentence described the misconception.…”
Section: Methodsmentioning
confidence: 99%
“…Students may distort or ignore new information that conflicts with their previous erroneous thinking . As a result, misconceptions can be a barrier to understanding, interfering with student learning …”
Section: Introductionmentioning
confidence: 99%
“…Few studies have specifically examined misconceptions. 2,3,5,8 Some studies in the areas of medicine, psychology and nursing have evaluated the interaction between confidence and correctness. 7,9,[11][12][13][14] Ibabe and Sporer 12 observed psychology students' theoretical assessments and showed that confidence varied as a function of question…”
mentioning
confidence: 99%
“…The huge growth in information in the modern society has made the application of statistical concepts very important [1,2,3]. However, some studies have found that learners usually hold some misconceptions about statistics which make them misunderstand the statistical concepts [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that learners usually hold some misconceptions about statistics which make them misunderstand the statistical concepts [3,4,5].…”
Section: Introductionmentioning
confidence: 99%